Clinical study of gatifloxacin in the treatment of male urethritis - Kawada, Yukimichi (Japanese Journal of Chemotherapy, 1999)
The clinical efficacies of gatifloxacin LX, a new 8-methoxyquinolone, on male urethritis were investigated. The subjects were 45 patients with gonococcal urethritis, 7 withgonococcal-chlamydial urethritis, 75 with chlamydial urethritis and 44 with nongonococcal-nonchlamydial urethritis. GFLX was administered orally at a dose of 200 mg twice a day for 3 days to the patients with gonococcal urethritis, and for 7 to 14 days to those with chlamydial urethritis and nongonococcal-nonchlamydial urethritis. Thirty-six patients with gonococcal urethritis, 33 patients with chlamydial urethritis and 20 patients with nongonococcal-nonchlamydial urethritis were assessable according to the criteria of the Japanese UTI Committee. The overall clinical responses were excellent in 30 cases and moderate in 6 cases with gonococcal urethritis, excellent in 25 cases, moderate in 7 cases and poor in 1 case with chlamydial urethritis, and excellent in all cases with nongonococcal-nonchlamydial urethritis, showing an overall efficacy rate of 100%, 97.0%, and 100%, respectively. MIC90 of GFLX against 36 strains of Neisseria gonorrhoeae isolated in this study, was 0.063μg/mL, and its activity was 4-to 8-times higher than that of ciprofloxacin and ofloxacin, respectively. The incidence of clinical adverse reactions was 3.8%(6/160), and of laboratory adverse reactions 6.0%(5/83), and all adverse reactions were slight in degree. The results suggest that GFLX is an effective and safe drug in the treatment of both gonococcal and chlamydial urethritis.